PARAMETRIC SHAPING OF CONSISTENT ARCHITECTURAL FORMS FOR BUILDINGS ROOFED WITH CORRUGATED SHELL SHEETING - ABRAMCZYK, Jacek (Architecture, Civil Engineering, Environment, 2017)
The paper presents a method for a parametric shaping of innovative building free forms covered with corrugated steel shell roofs and flat glass elevation walls. Each shell roof is made of plane steel sheets folded in one direction and transformed elastically into spatial shape. The obtained shapes can be really diversified sectors of various ruled surfaces. Therefore there is a great need for creating such a method that leads to a fine integration of the shapes of a free form shell roof and plane oblique elevation walls for each building free form. Thus, it was elaborated the innovative parametric method, whose algorithm allows for seeking attractive and consistent architectural free forms by means of computer programs. A relatively small set of initial relevant parameters enables the designer intuitively to affect the attractiveness of the designed free forms. Some special attention is paid to selected fine proportions of these geometrical parameters leading to the really attractive architectural free forms.